2010
DOI: 10.1002/ejoc.201000710
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Catalyzed Cycloisomerization and Tandem Oxycyclization/Hydroxylation of Alkynols: Synthesis of Nonfused, Spiranic and Fused Oxabicyclic β‐Lactams

Abstract: 2‐Azetidinone‐tethered alkynols, readily prepared from the corresponding aldehydes or ketones, were used as starting materials for the oxycyclization reaction catalyzed by precious metals. AgOAc exclusively affords dihydrofurans, methylenetetrahydrofurans, or methylenetetrahydro‐2H‐pyrans through specific 5‐endo, 5‐exo, or 6‐exo pathways, respectively. Interestingly, in the presence of a catalytic amount of PtII or AuIII salts, cyclization reactions occurred preferentially through a tandem oxycyclization/hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…At this stage, the reaction proceeds via as econd cyclization process involving the alkynyl lateral group and the oxygen to form the dihydrofuran cycle [23] which actually we computed to be extremelyt hermodynamically favored (DE = À119.16 kcal mol À1 ,see the Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…At this stage, the reaction proceeds via as econd cyclization process involving the alkynyl lateral group and the oxygen to form the dihydrofuran cycle [23] which actually we computed to be extremelyt hermodynamically favored (DE = À119.16 kcal mol À1 ,see the Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…33 It was found that the use of gold catalysis selectively led to a tandem cycloisomerization/hydroxylation, affording structures 36 and 39, while the use of silver-based systems yielded . PtBr 4 was also tested as catalyst for this procedure, providing similar results as the ones for gold.…”
Section: Scheme 10mentioning
confidence: 99%
“…22 In this context, the preparacion 19 of fused oxabicyclic β-lactams using gold catalysis through a tandem oxycyclization/hydroxylation of 2-azetidinone-linked alkynols has been accomplished. 23 The reaction of 2-azetidinone-tethered bishomopropargylic alcohol 40 in the presence of catalytic amounts of AuCl 3 provided bicycle 41…”
Section: Gold-catalyzed Oxycyclizations Of Alkynol Derivativesmentioning
confidence: 99%